KUALITAS PELAYANAN PUBLIK DALAM PERSEPSI PENERIMA LAYANAN: Studi pada Dinas Kependudukan dan Catatan Sipil Kabupaten Bogor - Subagdja, Oetje (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2021)
ABSTRACT The phenomenon raised as a research problem is the quality of Birth Certificate services organized by the Bogor Regency Population and Civil Registry Service which is still not optimal in its implementation, one of which is population data that is not comprehensive, not all accurate, and not all valid so that the performance of population administration services is still weak. The research was carried out according to the post-positivist paradigm (qualitative study). The population of this research is residents who have taken care of birth certificates and residents who are currently taking care of birth certificates at the Department of Population and Civil Registry of Bogor Regency. The community members are located in RW areas in 47 villages in Ciomas District, Ciawi District, Parung District, and Citeureup District. The research sample of 386 respondents was taken from a population of 1,115 people using the simple random sampling technique.  Data analysis used Frequency Distribution Analysis which was developed with Descriptive Analysis. The results showed that the respondents considered the quality of birth certificate services to be optimal and satisfactory in meeting the demands and expectations of the service recipients in terms of tangible, reliability, responsiveness, assurance, and empathy dimensions. Keywords: Public Service, Responsive, Service Recipient, Perception.  ABSTRAK Fenomena yang diangkat menjadi masalah penelitian adalah kualitas pelayanan Akta Kelahiran yang diselenggarakan oleh Dinas Kependudukan dan Catatan Sipil Kabupaten Bogor masih belum optimal dalam pelaksanaannya, salahsatunya data kependudukan yang belum menyeluruh, belum semua akurat dan tidak semua valid, sehingga masih lemahnya kinerja pelayanan administrasi kependudukan. Penelitian dilaksanakan menurut post positivist paradigm (study qualitative). Populasi penelitian adalah warga masyarakat yang pernah mengurus akta kelahiran serta warga masyarakat yang sedang mengurus akta kelahiran di Dinas Kependudukan dan Catatan Sipil Kabupaten Bogor. Warga masyarakat tersebut berada dalam wilayah RW pada 47 desa/kelurahan di Kecamatan Ciomas, Kecamatan Ciawi, Kecamatan Parung dan Kecamatan Citeureup.  Sampel penelitian 386 responden diambil dari populasi sebanyak 1.115 orang dengan simple random sampling technique. Analisis data menggunakan Analisis Distribusi Frekuensi yang dikembangkan dengan Analisis Deskriptif. Hasil penelitian menunjukkan bahwa para responden menganggap kualitas pelayanan akta kelahiran cukup optimal dan memuaskan dalam memenuhi tuntutan dan harapan pihak penerima layanan baik dari segi dimensi tangible, reliability, responsiveness, assurance dan empathy. Kata Kunci: Pelayanan Publik, Responsif, Penerima Layanan, Persepsi.  DOI : https://doi.org/10.33005/jdg.v11i2.2677